2014
DOI: 10.4172/2165-8056.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation and Recognition Specificity of the Avirulence Gene AvrPiz-T in Magnaporthe Oryzae Field Populations

Abstract: Magnaporthe oryzae, the rice blast pathogen, causes significant annual yield loss of rice worldwide. Currently, the most effective disease control approach is deployment of host resistance through introduction of resistance (R) genes into elite cultivars. The function of each R gene relies on the specific recognition of an avirulence (AVR) gene of the pathogen. However, the introduced resistance can be broken down within a few years, due to mutation of the AVR genes in the field populations. It is known from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 42 publications
(52 reference statements)
0
15
2
Order By: Relevance
“…The insertion of solo-LTR of retrotransposons Inago2 in promoter regions is predicted to change the avirulent function of the isolate 07-231-2a. Inago2 was founded at 41 bp upstream ORF in Chinese isolates without pathogenicity results (Chen et al, 2014). So, the inserting location and element of inago2 in this study are different from the previous study.…”
Section: Avrpiz-t Haplotypes Variance and Distributioncontrasting
confidence: 62%
See 4 more Smart Citations
“…The insertion of solo-LTR of retrotransposons Inago2 in promoter regions is predicted to change the avirulent function of the isolate 07-231-2a. Inago2 was founded at 41 bp upstream ORF in Chinese isolates without pathogenicity results (Chen et al, 2014). So, the inserting location and element of inago2 in this study are different from the previous study.…”
Section: Avrpiz-t Haplotypes Variance and Distributioncontrasting
confidence: 62%
“…A strong positive selection is detected at the locus. M. oryzae evades recognition of Piz-t gene in rice through diversification of its coding sequence and TEs in the promoter region of AvrPiz-t (Chen et al, 2014). In this study, at least nine haplotypes were identified based on AvrPiz-t gene (non-CDS and CDS, 2507 bp) from 312 M. oryzae isolates in Yunnan.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations